The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1074/jbc.m112.401158
|View full text |Cite
|
Sign up to set email alerts
|

Heterohexamer of 56- and 63-kDa Gene 4 Helicase-Primase of Bacteriophage T7 in DNA Replication

Abstract: Background:The role of the 56-kDa gene 4 helicase-primase in T7 DNA replication is unknown. Results: Individual hexamers of the 56-, 63-, or a mixture of the two have identical helicase activity. A mixture oligomerizes more efficiently than the 63-kDa protein.Conclusion: An equimolar mixture is optimal for coordinated DNA synthesis. Significance: The 56-kDa gp4 optimizes the ratio of primase to helicase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…One form is ~63 kDa containing both primase and helicase domains and another ~56 kDa truncated gp4 protein lacks the zinc binding domain of the primase. Recent studies have shown that these two proteins oligomerize and form a heterohexamers which show higher helicase activity than 63 kDa gp4 protein product alone (Zhang et al ., ). As PfPrex primase‐helicase domain shows primary sequence similarity with T7 bacteriophage gene 4 protein, it is possible that the two prominent forms of PfPrex helicase primase (~70 and ~55 kDa respectively) may have similar function like T7 gp4 protein.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…One form is ~63 kDa containing both primase and helicase domains and another ~56 kDa truncated gp4 protein lacks the zinc binding domain of the primase. Recent studies have shown that these two proteins oligomerize and form a heterohexamers which show higher helicase activity than 63 kDa gp4 protein product alone (Zhang et al ., ). As PfPrex primase‐helicase domain shows primary sequence similarity with T7 bacteriophage gene 4 protein, it is possible that the two prominent forms of PfPrex helicase primase (~70 and ~55 kDa respectively) may have similar function like T7 gp4 protein.…”
Section: Resultsmentioning
confidence: 97%
“…The polymerase domain of PfPrex is separated from the primase–helicase domain but whether the primase–helicase domain works as a complex or individually is not known. Interestingly, in T7 bacteriophage, two forms (63‐kDa full‐length gp4 and 56‐kDa truncated gp4) of gene4 protein (gp4, primase‐helicase) are expressed and together they form heterohexamer to perform as a fully functional protein (Zhang et al ., ). It is possible that P .…”
Section: Introductionmentioning
confidence: 97%
“…Western blot analysis has identified numerous cleavage products of Prex, although it is not clear which represent functional proteins. It is possible there are several forms of the mature active Prex proteins, as multiple isoforms of the bacteriophage T7 primase-helicase have been observed [28]. Identification of the protease(s) responsible for separating the Prex primase, helicase, and polymerase domains would lead to a better understanding of posttranslational modifications of apicoplast proteins and identify potential new drug targets.…”
Section: Prex (Transcription Transport and Processing)mentioning
confidence: 98%
“…The hexameric gp4 has primase activity on its N-terminus to initialize Okazaki fragment synthesis, and Hel activity on its C-terminus to unwind the dsDNA. The Hel domain on gp4 is a member of the superfamily 4 (SF4) Hels and uses the energy from ATP or dTTP hydrolysis to migrate in the 5′-to-3′ direction on the lagging strand DNA [ 20 , 21 ]. The tight DNA binding by gp4 helicase domains promotes substrate engagement of the primase [ 20 ].…”
Section: Hel–pol Coupling In Bacteriophage T7 Dna Replicationmentioning
confidence: 99%